Visual Politics in the Digital Age: The Impact of Instagram Formats on Political Participation Driven by Influencers - Palacios López, Maitane; Bonete Vizcaíno, Fernando (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
In the process of Instagram’s consolidation as a visual platform, political influencers are emerging as new agents in the creation of political content. Based on the study of 750 posts from 30 prominent political influencers in Spain, this research analyzes how interaction metrics influence the formats of Reels and Posts, exceeding benchmark averages (Sehl & Mikolajczyk, 2024). The choice of format not only shapes the type of visual political content disseminated but also influences the consumption and political participation practices of young audiences, highlighting the importance of interaction metrics in the success of digital content.